2022
DOI: 10.1111/tmi.13794
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with surgical repair success of female genital fistula in the Democratic Republic of Congo: Experiences of the Fistula Care Plus Project, 2017–2019

Abstract: Objective: We sought to document outcomes and factors associated with surgical success in hospitals supported by the Fistula Care Plus Project in the Democratic Republic of Congo (DRC), 2017-2019. Methods: This was a retrospective cohort study analysing routine repair data on women with Female Genital Fistula. Univariate and multivariate analyses were conducted to determine factors associated with successful fistula repair. Results: A total of 895 women were included in this study, with a mean age of 34 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…In the present study, there was a high success rate of OFs repair which was similar to a study reported by other Congolese (71.7%-89.2%) [2,15,24,26,27] and African (77.9%-84.76%) [18,22,28] studies. The success rate after surgical fistula repair varies from centre to centre and is determined by many factors such as fistula site, degree of healing, previous repair attempts, surgical repair technique, surgeon's expertise, equipment and post-operative nursing among others.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, there was a high success rate of OFs repair which was similar to a study reported by other Congolese (71.7%-89.2%) [2,15,24,26,27] and African (77.9%-84.76%) [18,22,28] studies. The success rate after surgical fistula repair varies from centre to centre and is determined by many factors such as fistula site, degree of healing, previous repair attempts, surgical repair technique, surgeon's expertise, equipment and post-operative nursing among others.…”
Section: Discussionsupporting
confidence: 92%
“…Several factors can explain this observation in the DRC such as the low proportion of obstetricians who are poorly distributed over the vast territory, the low investment in the continuing education of young doctors who find themselves alone in isolated places, the poor equipment of public hospitals, road infrastructure in continuous deterioration, the inadequate health referencing system, the continuous deterioration of the socio-sanitary conditions of the Congolese population, etc. [2,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 Evidence shows that most attributes of OF repair failure are confined to the characteristics of the fistula rather than that of the patient. 9,16 For instance, it is associated with the fistula size, 11,13,14,17,18 duration of bladder catheterization, 14,17 dura tion of labor, 13,14,19 repair site, 17 previous repair attempts, 12,[17][18][19] type of fistula, 14 post-operation infection, 13 duration of fistula, 19 and bladder destruction. 13 OF repair procedures have been conducted for centuries; 20 however, little attention has been paid globally.…”
Section: Introductionmentioning
confidence: 99%